Cell‐Penetrating Peptides Containing Fluorescent d‐Cysteines. Issue 31 (8th May 2018) - Navo, Claudio D.; Asín, Alicia; Gómez‐Orte, Eva; Gutiérrez‐Jiménez, Marta I.; Compañón, Ismael; Ezcurra, Begoña; Avenoza, Alberto; Busto, Jesús H.; Corzana, Francisco; Zurbano, María M.; Jiménez‐Osés, Gonzalo; Cabello, Juan; et al.
Abstract: A series of fluorescentd ‐cysteines (Cys) has been synthesized and their optical properties were studied. The key synthetic step is the highly diastereoselective 1, 4‐conjugate addition of aryl thiols to a chiral bicyclic dehydroalanine recently developed by our group. This reaction is fast at room temperature and proceeds with total chemo‐ and stereoselectivity. The Michael adducts were easily transformed into the corresponding amino acids to study their optical properties and, in some selected cases, into the corresponding N ‐Fmoc‐d ‐cysteine derivatives to be used in solid‐phase peptide synthesis (SPPS). To further demonstrate the utility of these non‐natural Cys‐derived fluorescent amino acids, the coumaryl and dansyl derivatives were incorporated into cell‐penetrating peptide sequences through standard SPPS and their optical properties were studied in different cell lines. The internalization of these fluorescent peptides was monitored by fluorescence microscopy. Abstract : Fluorescentd ‐cysteines : The efficient synthesis of enantiopure and fluorescentd ‐cysteines is reported by using highly chemo‐ and stereoselective S ‐Michael additions of thiol‐containing dyes on a chiral bicyclic dehydroalanine. Their use as fluorescent labels was validated by incorporation into cell‐penetrating pentapeptides, which were treated with different HeLa cell lines, monitoring their internalization by fluorescence microscopy.